Uptake and Biological Effects of Environmentally Relevant Concentrations of the Nonsteroidal Anti-inflammatory Pharmaceutical Diclofenac in Rainbow Trout (Oncorhynchus mykiss) - Mehinto, Alvine C; Hill, Elizabeth M; Tyler, Charles R (Environmental science & technology, 2010)
Diclofenac, a nonsteroidal anti-inflammatory drug, is widely detected in surface waters and can potentially cause deleterious effects in fish. Here, we investigated the biological effects of 21-day exposure to waterborne diclofenac at environmentally relevant concentrations (0, 0.5, 1, 5, and 25 μg/L) in rainbow trout. Accumulation of diclofenac in the bile was measured and responses in selected tissues were assessed via changes in the expression of selected genes (cytochrome P450 (cyp) 1a1, cyclooxygenase (cox) 1 and 2, and p53) involved in metabolism of xenobiotics, prostaglandin synthesis, and cell cycle control, respectively, together with histopathological alterations in these tissues. Diclofenac accumulated in the bile by a factor of between 509 ± 27 and 657 ± 25 and various metabolites were putatively identified as hydroxydiclofenac, diclofenac methyl ester, and the potentially reactive metabolite hydroxydiclofenac glucuronide. Expression levels of both cox1 and cox2 in liver, gills, and kidney were significantly reduced by diclofenac exposure from only 1 μg/L. Expression of cyp1a1 was induced in the liver and the gills but inhibited in the kidney of exposed fish. Diclofenac exposure induced tubular necrosis in the kidney and hyperplasia and fusion of the villi in the intestine from 1 μg/L. This study demonstrates that subchronic exposure to environmental concentrations of diclofenac can interfere with the biochemical functions of fish and lead to tissue damage, highlighting further the concern about this pharmaceutical in the aquatic environment.